Hubungan Motivasi dan Pola Menonton dengan Tingkat Kepuasan Pemirsa pada Program Berita Topik ANTV (Kasus Pemirsa di Komplek Perumahan Pondok Sukatani Permai, Tapos, Kota Depok) - Marwan Albab; Amiruddin Saleh (Institut Pertanian Bogor, 2013)
ABSTRACT Television is most effective mass media to transfer information to audience than print media. Recently, people use television not only to get entertainment but also information. One of television programme that content more information and knowledge is news programme. ANTV become one option which can be a source of recent information and science for audiences. Based on uses and gratification theory, the audiences were looked actively in using mass media to fulfill their need. It means that someone use mass media because of certain motive. Mass media application offer expectable satisfaction for audience. The audiences behavior in applying media continually will increase day after day, in which they get satisfaction. It called by pattern of watching. Therefore, this research examine relationship between motivation, pattern of watching and satisfactory rate of audiences on Topik ANTV news programme. This research was done by a quantitative survey using a desciptive correlational design. Respondent were audiences in Komplek Perumahan Pondok Sukatani Permai, Tapos Distric, Depok City, and it selected by proportional stratified random sampling technique. Data were processed by the Spearman correlation test with SPSS for windows version 18. Motivation and pattern of watching shows option had a highly significant relation (p<0,01) with whole aspects of motivation for each them. Motivation with satisfaction shows option had significant relation (p<0,05) and the pattern with satisfaction shows option had highly significant relation (p<0,01). Keywords: news programme, motivation, patterns of watching, satisfaction